Road Transportation Development and Land Use Changes in Semarang City, Central Java, Indonesia - Endah Sri Hartatik; Wasino Wasino; Edy Trihatmoko (Faculty of Geography, Universitas Gadjah Mada, 2022)
This research aims to make a historical mapping of the development of road infrastructure and the impact on land use changes. A historical analysis was conducted based on the documents and reports of transportation development, road construction, and urban planning in Semarang City, the capital city of Central Java, Indonesia. From a historical perspective, the transportation development and the land use change of Semarang City were determined by economic activities from the early period of colonialism, especially when this city was devoted as a port city in Java with massive coastal inhabitants. Along with this economic activity, ports and roads were built, accelerating the city’s development until the mid of 20th century. Road construction generated urban problems such as rapid urbanization, and environmental problems. Meanwhile, the road construction also accelerated the city agglomeration, connecting Semarang City with other cities on the Java North Coast. However, in the 1990s the symptom of the use of private transportation occurred in Semarang which became the most critical issue in the later periods.